GC-MS/MS Determination of Steroid Hormones in Urine Using Solid-Phase Derivatization as an Alternative to Conventional Methods - Azamat Temerdashev; Pavel Nesterenko; Ekaterina Dmitrieva; Kseniya Zhurkina; Yu-Qi Feng (Molecules, 2022)
Solid-phase analytical derivatization (SPAD) is a promising hybrid sample preparation technique combining the clean-up and preconcentration of the sample in a single step. In this work, a novel SPAD method based on the preparation of trimethylsilyl (TMS) derivatives of steroid hormones (testosterone, estrone, DHT, estriol, estradiol, and progesterone) in Phenomenex Strata C18-E (100 mg, 1 mL) cartridges has been developed and applied for their GC-MS/MS determination in human urine samples. The proposed procedure allows the detection and quantification of steroids with limits of 1.0–2.5 and 2.5–5 ng/mL, respectively. These characteristics are comparable with those obtained with a conventional liquid–liquid extraction, while the recovery of analytes in the proposed SPAD procedure is higher. The major advantages of SPAD are a short derivatization time, high efficiency, and the possibility to automatize the procedure. However, its cost-effectiveness in routine practice is still questionable.